Highly performing ionic liquid enriched hybrid RSDs. Issue 25 (6th June 2017) - Rajan, Krishna; Bejtka, Katarzyna; Bocchini, Sergio; Perrone, Denis; Chiappone, Annalisa; Roppolo, Ignazio; Pirri, Candido Fabrizio; Ricciardi, Carlo; Chiolerio, Alessandro
Abstract : Real-time observation of the filament formation and annihilation (grey area corresponds to tungsten nanoprobe). (a) Filament formation at set threshold (orange color path corresponds to the formed filamentary path). (b) Filament dissolution at reset threshold (magenta color corresponds to the annihilation of the filamentary path). (c) Further filament formation. Abstract : A simple two terminal planar resistive switching device (RSD) is fabricated with a 10 µm active gap. The active hybrid matrix is based on a PEO, Ionic Liquid and Silver Nitrate formulation which represents a perfect polymeric medium for the growth of a conducting filament, whose creation/destruction is due to the migration of silver ions within the matrix. Two different device configurations are compared based on the electrode symmetry. The first case includes a planar symmetric device with electron beam evaporated gold electrodes, while the second is based on a planar asymmetrical device with sputtered platinum and electron beam evaporated silver electrodes. The asymmetric device exhibits a continuous resistive switching up to 500 cycles by maintaining an outstanding on/off ratio of 10 4 throughout the test without any compromise in its retention. The fabrication of reliable soft (hybrid) materials is of paramount importance for the development of next generation wearable devices that must be stretchable and flexible; planar microelectronic systems, better than stacked ones, are compatible with high throughput production technologies such as printing, where uniformity is controlled on a higher scale in comparison to standard lithographic processes. The present work provides clear-cut evidence of the conducting filament formation/dissolution during the resistive switching process of a soft material. A detailed explanation is given on the formation and rupture of the same.